Cavum Vergae: In the Differential Diagnosis of Fetal Midline Intracranial Cystic Lesions - Demirel, Emine; Subasioglu, Aslı; Kalayci, Tugce Ozlem; Birlik, Bilge Ince; Turhan, Ugur; Kelekci, Sefa (Journal of Pediatric Neuroradiology, 2015)
Cavum vergae (CV) cysts are developmental cysts of the midline of the brain that is formed from the posterior extension of the cavum septum pellucidum. Several cases of enlarged CV have been reported previously, but prenatal diagnosis of this condition is very rare. We report a case of isolated dilated CV diagnosed prenatally. When midline intracranial cysts are determined prenatally, first physicians must pay attention to distinguish them from pathologic cyst and determine whether associated malformations are present or not. The sonography is a useful tool for both the differential diagnosis and identification of associated malformations. Although CV may be present as a normal variation without clinical findings, it has been also considered as a marker of impaired neurodevelopment. Although the relationship between the CV and the various clinical findings such as headache, papilla edema, cognitive and behavior disorders, and psychiatric problems has not been fully elucidated, an accurate evaluation will be helpful for estimation of prognosis, the assessment of the risk for the other related malformations, and for the follow-up of the patient. Also, it is important to identify these kinds of findings, to clarify their clinical importance and for genetic counseling.
Keywords: brain; cavum septum pellucidum; cavum vergae; cyst; prenatal diagnosis